An empirical investigation of end-users’ switching toward cloud computing: A two factor theory perspective - Park, Sang Cheol; Ryoo, Sung Yul (Computers in Human Behavior, 2013)
With the diffusion of cloud services, they are becoming an alternative to traditional information technology (IT). Despite the importance of cloud services, relatively few studies have been devoted to an empirical examination of the switching behavior from traditional IT to cloud services at the individual level. Therefore, this study attempts to explore the switching factors (i.e. switching enablers and switching inhibitors) and to empirically examine the relationships between those and users’ intention to switch to cloud services, based on the two-factor theoretic perspective. This study uses a longitudinal design to get survey data from undergraduate students at two universities in Korea in the context of IT switching to Google Apps settings. According to our findings, this study found that users’ switching intention to cloud services was not only positively influenced by expected switching benefits whose antecedents are omnipresence of cloud services and collaboration support, but also negatively influenced by expected switching costs whose antecedents are satisfaction with incumbent IT and breath use of inclement IT. The impacts of switching benefits and costs on switching intention were also positively moderated by end users’ personal innovativeness.